Efficacy of Tagetes erecta (L.) Aqueous Leaf Extract against the Root Knot Nematode Meloidogyne incognita: In vitro - Manimegalai.T; S. Iruthaya Kalai Selvam (The Bioscan, 2025)
Root knot nematodes (Meloidogyne incognita) are among the most destructive soil borne pathogens of vegetable crops, causing severe yield losses worldwide. In the present study, Meloidogyne incognita was identified based on microscopic examination of mature females, which exhibited diagnostic features including a pear shaped body, distinct stylet, thick cuticle, and a squarish dorsal arch with wavy forked striae in the perineal pattern. In vitro assays revealed that aqueous leaf extract of Tagetes erecta (L.) exhibited significant nematicidal activity against second stage juveniles (J₂) of M. incognita. Juvenile mortality increased with extract concentration, reaching 100% at 1000 ppm, followed by 89%, 72%, 61.5%, 51.5%, and 18.5% at 800, 600, 400, 200, and 100 ppm, respectively. Statistical analysis (one-way ANOVA) confirmed significant differences (p < 0.05, p < 0.01, p < 0.001) among treatments compared to the control. Probit analysis further revealed a progressive decline in LC50 values with increasing exposure time, from 220.85 ppm at 24 h to 120.45 ppm at 96 h, indicating enhanced nematicidal efficacy over time. These findings demonstrate that T. erecta (L.) leaf extract shows significant nematicidal potential and could serve as an effective botanical alternative for managing root knot nematodes.